Pengaruh Disiplin Kerja, Motivasi Finansial Dan Budaya Organisasi Terhadap Prestasi Kerja Karyawan Pada CV. SINEZ - Cancerina, Yunie (E-Jurnal Manajemen, 2013)
The purpose of this research is to know the positive relation partially and simultaneously  from free variable against variable which are bounded in CV. Sinez. CV. Sinez located in  West Gatot subroto street no.900x Denpasar, Bali. The number of  total respondents are 59 people. The method of data analysis that being used is a factor analysis and double linear regression using program spss. The result of this research indicated that variable employee accomplishments was affected by work discipline ,financial motivation and cultural organization simultaneously. Partial assay results shows that employees accomplishments variable was affected positively by work discipline, financial motivation and cultural organization. Financial motivation variable is the most domineering variable which affected the work performance an employee at CV. Sinez.   Key words: work discipline, financial  motivation, organizational culture, employee accomplishments